GAMBARAN RESILIENSI PEREMPUAN PENYINTAS KEKERASAN SAAT PACARAN - Susanti, Helen; Adhyatma, Made Dharmawan Rama (Jurnal Psikologi Poseidon, 2023)
Resilience is the ability that a person uses to develop and adapt to the problems that arise in his life. This ability can be developed and trained. Resilience can be possessed by individuals who have experienced dating violence and resilience is considered a person's ability to solve past problems and open a new page in his life. Violence is the act of a person or group of people that causes injury or death to another person or causes physical or property damage to another person. In this study, violence was perpetrated by the ex-boyfriend of the victim of violence and the purpose of this study was to see how resilience is described in survivors of violence during dating. The method used is a qualitative research method using a phenomenological approach and using deductive analysis. The sampling technique used is purposive sampling. The informants in this study were two women who had experienced violence during dating. Each individual has a different experience of dating violence, so each has a different experience of resilience. The results of this study are that each informant shows a resilience experience that allows them to survive until now.